Effect of Quran on promoting the eating habits and physical activity of adolescents: using the theory of planned behavior - Farkhondeh sadat Torabi (Journal of Research & Health, 2015)
Bakground: Today, the effect of education on life style by applying theories has been proven in different studies.The purpose of this study is Effect of Quran’s Teachings on Healthy Eeating Habits and Physical Activity of Gonabad Students using theory of planned behavior and Comparison of It between Boys and Girls in 2013. Methods: In this quasi-experimental study (pretest-posttest without control group) eighty 12-15 years old students were selected by multi stage cluster random sampling. First, the samples completed eating habits and physical activity questionnaire based on constructs of theory of planned behavior,then received a five sessions course with content of Quran’s teachings based on the theory’s constructs. Four weeks after the last intervention post test was done and data were analyzed by SPSS version 20 and paired and independent t-tests and multi factorial regression. Results: Results showed Quran’s teachings has positive effect on healthy eating habits (p< 0.001) and physical activity (p< 0.001) in all constructs theory of planned behavior. Also, there was significant difference in intention to healthy eating (p= 0.017) and physical activity behavior (p= 0.013) between boys and girls,The boys had higher levels of physical activity and healthy eating habits than girls. Regression results have revealed intention was the most anticipant for healthy eating behavior in boys (B= 0.831) and girls (B= 0.529). There was no significant relation between intention and physical activity behavior, it was anticipated with perceived behavioral control in boys (b= 0.628) and subjective norms in girls (B= 0.882). Conclusion: In regard to results of this study, Quran’s teachings using theory of planned behavior has important effect on improving students’ healthy eating habits and physical activity and educational program for the adolescents must tailored to gender to obtain the optimum result